Identification of logical extra-ribosomal functions mediated by the ribosomal protein genes, RPS3 and RPS12 via In Silico approach - Nazatul Syahira, bt. Roslan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Ribosomal proteins (RPs) are the main component of ribosomes and play important roles in protein biosynthesis. Besides, several of them are shown to have extraribosomal functions. In this research, we used bioinformatics approach in finding the interaction between the ribosomal protein S3 (RPS3) and ribosomal protein S12 (RPS12) with their protein partners. Our results discovered that RPS3 interacts with Epidermal Growth Factor Receptor (EGFR) and 14-3-3 protein epsilon (YWHAE). RPS3 is predicted to inhibit the function of EGFR and YWHAE. RPS12 interacts with Transcription Elongation Factor B Polypeptide (ELOB) and Ski-like protein (SKIL). Hence, it is predicted to interrupt the function of ELOB and SKIL.